Optimal detection and parameter estimation for sinusoidal signals - Wang, Qing. (2008)
This thesis addresses the optimal detection and parameter estimation for sinusoidal signals with unknown parameters embedded in Gaussian noise with unknown variance, which is a principle issue in signal processing with many applications.